Discount Vouchers and Perceived Benefits: Decision to Use Grabfood Online Food Ordering Application in Semarang City - Nugroho, Aditiya Pratama; Putri, Adelia Sandra Swastika; Prabowo, Heri (Klabat Journal of Management, 2025)
This study examines the influence of discount vouchers and perceived benefits on consumer decisions to use the GrabFood online food ordering application in Semarang, Indonesia. The research seeks to analyze how these factors interact to shape user behavior, offering insights for optimizing marketing strategies in the competitive food delivery sector. Using a quantitative approach and Structural Equation Modeling Partial Least Squares (SEM-PLS) for data analysis, the study collected responses from 130 GrabFood users in Semarang. The findings indicate that both discount vouchers and perceived benefits significantly impact consumers’ decisions to adopt GrabFood. Discount vouchers not only directly enhance perceived financial savings but also strengthen users’ perceptions of the overall value of the service, thereby encouraging app usage. Additionally, perceived benefits, such as convenience and service quality, mediate the relationship between discount vouchers and user decisions. These results underscore the importance of strategic pricing and effective value communication in driving user engagement and retention within the food delivery industry